Evaluando la utilización de Internet para desarrollar innovación en las empresas con mayor capacidad de aprendizaje - Julio García del Junco; Georg Dutschke; Beatriz Palacios Florencio (Colegio de Economistas de A Coru\~na, 2010)
– The objective of this study was to test the hypothesis of relationship between learning ability and use of the Internet for information search and development of new learning. For this analysis develops a model based on the work of organizational learning Senge (1990), Kim (1993), Mintzberg and Quinn (1996), Probst and Buchel (1997), Argyris (1999), Carneiro et al. (2001) and Serrano and Fialho (2005). The methodology consisted in a questionnaire with which to assess the relevant factors in the model, taking into account the views of various parties interested in research (academic and corporate), the completion of fieldwork and subsequent statistical analysis . The results show that organizations with greater capacity for learning more functionality using the Internet to generate new knowledge and develop new learning.
Keywords: M10; 330; Learn; organization; Internet